VITEREACT: STREAMLINED STATIC SITE GENERATION WITH REACT (CAHIERS MAGELLANES-NS, 2024)
Static websites are used to build content-driven websites. They offer ease of development, low-security risks, and can generate value quickly due to informational content being quite significant. With the rising need for content marketing, dynamic websites became popular as they allow one to present actual information. All of this comes at the cost of impacting page loading speed which is also very important for content-centric websites. Static site generators (SSGs) aim to solve this issue. SSG is a tool to build a static website from raw markdown files. It adds more flexibility to static websites allowing them to react to dynamic content changes, regenerate, and publish again. The proposed system is an implementation of a static web page generator.This study presents the development and evaluation of a Static Site Generator (SSG) built using Vite, a modern build tool for web development, and React, a popular JavaScript library for building UI. Leveraging the efficiency and flexibility of Vite and the component-based architecture of React, our SSG aims to streamlinewebsite development and enhance performance.The outcomes of our implementation include improved website speed, enhanced user experiences, and simplified development workflows. By adopting these modern technologies, we demonstrate how SSGs can benefit from cutting-edge tools and frameworks to meet the demands of modern web development practices.Vite's innovative build pipeline leverages modern JavaScript module bundling techniques, such as ES modules (ESM), to optimize the generation of static assets. Unlike traditional bundlers, which bundle all dependencies into a single JavaScript file, Vite generates optimized assets on-demand, only bundling the specific modules required for each page or component. This approach eliminates unnecessary bundling and reduces bundle sizes, resulting in faster load times and improved website performance. Additionally, Vite's support for server-side rendering (SSR) enables seamless integration with React components, allowing developers to leverage the power of React for building dynamic and interactive UI within static websites.